Downregulation of Plasma Membrane Ca2+ ATPase driven by tyrosine hydroxylase-Gal4 reduces Drosophila lifespan independently of effects in neurons - Brenda Erhardt; Lia Frenkel; María Silvina Marcora; María Isabel Farías; Carina Cintia Ferrari; Fernando Juan Pitossi; María Celeste Leal (Fly, 2023)
In Drosophila melanogaster, several Gal4 drivers are used to direct gene/RNAi expression to different dopaminergic neuronal clusters. We previously developed a fly model of Parkinson’s disease, in which dopaminergic neurons had elevated cytosolic Ca2+ due to the expression of a Plasma Membrane Ca2+ ATPase (PMCA) RNAi under the thyroxine hydroxylase (TH)-Gal4 driver. Surprisingly, TH-Gal4>PMCARNAi flies died earlier compared to controls and showed swelling in the abdominal area. Flies expressing the PMCARNAi under other TH drivers also showed such swelling and shorter lifespan. Considering that TH-Gal4 is also expressed in the gut, we proposed to suppress the expression specifically in the nervous system, while maintaining the activation in the gut. Therefore, we expressed Gal80 under the direction of the panneuronal synaptobrevin (nSyb) promoter in the context of TH-Gal4. nSyb-Gal80; TH-Gal4>PMCARNAi flies showed the same reduction of survival as TH-Gal4>PMCARNAi flies, meaning that the phenotype of abdomen swelling and reduced survival could be due to the expression of the PMCARNAi in the gut. In perimortem stages TH-Gal4>PMCARNAi guts had alteration in the proventriculi and crops. The proventriculi appeared to lose cells and collapse on itself, and the crop increased its size several times with the appearance of cellular accumulations at its entrance. No altered expression or phenotype was observed in flies expressing PMCARNAi in the dopaminergic PAM cluster (PAM-Gal4>PMCARNAi). In this work we show the importance of checking the global expression of each promoter and the relevance of the inhibition of PMCA expression in the gut.